Evaluation of broiler partnership program with importance performance analysis in Kampar District, Riau Province - Fitra, Deni; Irawati, Evi; Tribowo, Hendro; Robiwala, Gusti (Faculty of Animal Science, Universitas Brawijaya, 2020)
This study aimed to evaluate the performance of broiler partnership program with importance performance analysis (IPA) approach and analyze its performance attributes that need to be improved and maintained in Kampar Regency, Riau Province. This descriptive study was done by using survey research methods on plasma farmers who has partnered with poultry companies, consisted of 30 plasma farmers in partnership with foreign capital companies, 10 plasma farmers in partnership with multinational companies and 6 plasma farmers in partnership with local companies. The samples were selected with purposive sampling method. The results of this study showed that the average service performance of the foreign capital partnership was 94.57 (very good), the multinational partnership was 95.22 (very good), while the local company partnership was 66.44 (good). Moreover, the local company partnership showed poor attributes on the feed quality and compensation. The service attributes that should be maintained by the foreign capital partnership were the suitability of harvest time, the response to all complaints, the suitability of output prices and the provision of compensation. Multinational partnership service attributes that should be maintained were the application of DOC contract prices, suitability of harvest time, response to all complaints, suitability of output prices, bonus price, and compensation. Moreover, the attributes of the services by the local company partnership that should be maintained were the drugs and vaccines qualities, technical guidance frequency as well as services and guidance material.